Benefits of Joining a Chorale on Self-Esteem and Social Relationship of Holy Family Parish: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The idea of a virtual chorale, started by Eric Whittaker in 2009, was inspired by the virtualchorale that took place in the United Arab Emirates during the COVID-19 pandemic. Thisvirtual chorale was successful due to the participation of precisely 117,572 singers from 129countries. Due to its wide range of multiple benefits to an individual, researchers believe thatsinging is not the only thing that keeps people from participating in a chorale. However, recentstudies have failed to demonstrate the benefits of choir participation in areas of self-esteemand involvement of an individual through social relationships as an individual's overalldevelopment. The study aims to know the benefits of joining the chorale associated with thesignificant benefits in the areas of self-esteem and social relationships. The research objectiveis to determine the benefits it has on the respondents’ sense of self-belongingness, self-confidence, self-identity, and relationship with their immediate family, friends, and thecommunity.The research supported the objective of the study of determining the benefits that the choralehas on the respondents’ sense of self-belongingness, self-confidence, self-identity, andrelationship with their immediate family, friends, and the community. With the result acquiredfrom the data, it was found that self-identity was the most beneficial component among othercomponents of self-esteem and social relationships given in the study.After the research was conducted, this study concludes that there is a significant benefit onself-esteem and social relationships among the chorale members of Holy Family Parish. Thisstudy reveals that participating in a choir is highly beneficial to the self-esteem and socialrelationship involvement of the choir members.
Keywords: Psychology